Refractory material for hydrogen energy glass kiln and preparation method thereof

By using Re/Co/Cs-LDH@CuO nanowires as additives for refractory materials in hydrogen-energy glass kilns, the problems of material corrosion and temperature changes in high-temperature environments of hydrogen-energy glass kilns are solved, and the high-temperature stability and oxidation resistance of the material are significantly improved.

CN119751030AActive Publication Date: 2025-04-04QINHUANGDAO GLASS IND RES & DESIGN INST

Patent Information

Application Number
CN202411970846.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Hydrogen-energy glass kilns require refractory materials to resist corrosion and frequent temperature changes in high temperature environments, and existing materials do not perform well in this environment.

Method used

Re/Co/Cs-LDH@CuO nanowires are used as additives for refractory materials, and the toughness and thermal shock resistance of the material are improved by covering Re, Co and Cs metal nanoparticles on the outer layer of the copper oxide nanowires.

Benefits of technology

It significantly improves the stability and oxidation resistance of refractory materials in high temperature environments, and enhances its cracking and damage resistance in frequent temperature changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751030A_ABST
    Figure CN119751030A_ABST
Patent Text Reader

Abstract

In order to promote the hydrogen energy glass kiln more quickly, research and development of the refractory material for the hydrogen energy glass kiln have important significance. The invention belongs to the field of refractory material preparation, and particularly relates to a refractory material for a hydrogen energy glass kiln and a preparation method of the refractory material. The refractory material prepared by the invention can stably work for a long time in a high-temperature environment, does not generate obvious phase change or decomposition, has good thermal shock resistance, can bear frequent temperature change, shows excellent oxidation resistance in a hydrogen combustion environment, prevents the surface of the material from being oxidized and eroded, and has good thermal shock resistance. And moreover, the mechanical strength and the wear resistance are high, and the reliability and the durability of the material under severe working conditions are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a refractory material for a hydrogen energy glass furnace and a preparation method thereof. Background Art

[0002] Glass is mainly made of quartz sand and soda ash as raw materials through high-temperature melting. Glass kiln is the equipment for melting glass, and there are many types of glass kilns. Hydrogen glass kiln is a high-temperature equipment that uses hydrogen as the main fuel. It is used for melting, clarification and homogenization in the glass manufacturing process. Compared with traditional fossil fuels (such as natural gas or heavy oil), hydrogen energy has the advantage of zero carbon emissions, so it is of great significance in achieving industrial decarbonization goals. Hydrogen has high calorific value combustion characteristics. The calorific value of hydrogen is about 142MJ / kg, which is more than twice that of natural gas, and can provide higher heat output. The combustion product of hydrogen is mainly water vapor, and theoretically no carbon dioxide (CO2) and nitrogen oxides (NO x ) and sulfur oxides (SO x ), which helps reduce environmental pollution. Hydrogen can be burned directly to heat the glass raw materials in the kiln, similar to the way traditional fuels are used. Combined with electric heating technology, energy utilization efficiency and temperature control accuracy can be further improved. The advantages of hydrogen glass kilns are that they are environmentally friendly and hydrogen combustion does not produce CO2, which is in line with the goal of global carbon neutrality. Compared with traditional fuels, hydrogen combustion produces almost no other harmful gases. The high calorific value of hydrogen means that less fuel consumption can achieve the same heating effect. Hydrogen burns quickly and can quickly increase the kiln temperature and shorten the heating time. Hydrogen kilns can flexibly adjust operating parameters to meet the production needs of different types and scales of glass. However, the high temperature and water vapor generated by hydrogen combustion may corrode the kiln materials, and new high-temperature and corrosion-resistant refractory materials need to be developed. Frequent temperature changes may cause cracks or breakage in the kiln materials, and the thermal shock resistance of the materials needs to be improved. Therefore, the refractory materials used in hydrogen glass kilns need to have excellent high-temperature stability, thermal shock resistance and oxidation resistance to adapt to the high-temperature environment generated by hydrogen combustion and possible rapid temperature changes. As an emerging clean energy technology, hydrogen glass furnace has great potential in achieving industrial decarbonization. In order to promote hydrogen glass furnace faster, it is of great significance to develop a refractory material for hydrogen glass furnace. Summary of the invention

[0003] In view of the above problems, the present invention provides a refractory material for a hydrogen energy glass furnace and a preparation method thereof. The specific preparation method is as follows:

[0004] S1. Take 5-12mL of hydrochloric acid, dilute it to 20-33mL with ethanol, immerse the copper foil until the solution turns yellow, take out the copper foil, rinse it with ethanol, then immerse it in acetone for 5-11min, rinse it with ethanol, then immerse it in ethanol for 8-16min, and you can get a clean copper foil; all solutions in this step need to be prepared before use to avoid re-oxidation.

[0005] S2. Weigh 2-3 g of sodium hydroxide and 0.15-0.5 g of ammonium thiosulfate, dissolve them in 12-23 mL of deionized water, immerse the copper foil treated in step S1, soak for 8-15 minutes, take out and rinse, and you can get Cu(OH)2 nanowires. Then calcine in a muffle furnace at 320-410°C for 1.5-3.1 hours to obtain CuO nanowires. In this step, calcining the Cu(OH)2 nanowires in the muffle furnace is to quickly dehydrate and prepare more resilient CuO nanowires.

[0006] S3, 0.61-0.83mmol of cobalt nitrate, 0.23-0.44mmol of cesium chloride, 0.23-0.44mmol of ammonium perrhenate and 0.3-0.5g of hexamethylenetetramine are dissolved in 33-45mL of deionized water, stirred for 12-23min, and the CuO nanowires prepared in step S2 are added, soaked for 12-16min, and then transferred to a reactor together, calcined at 118-148℃ for 8-10h, and after cooling, the copper foil with the material is taken out and immersed in ethanol, ultrasonically peeled for 1h, and centrifuged and dried to obtain Re / Co / Cs-LDH@CuO. This material utilizes the one-dimensional structure of copper oxide nanowires, and the outer layer of the nanowires is coated with Re, Co and Cs metal nanoparticles. The three metal particles are uniformly attached to the nanowires through hydrothermal reaction. As an additive for refractory materials, it can improve the toughness and thermal shock resistance of refractory materials to ensure that the refractory materials will not crack or break in frequent temperature changes.

[0007] S4, 5-7g of Re / Co / Cs-LDH@CuO prepared in step S3, 33-41g of aluminum oxide, 5-8g of silicon dioxide, 11-13g of zirconium oxide, 4-6g of mullite, 17-23g of silicon carbide, 6-8g of cerium dioxide, 7-11g of titanium oxide, 2-5g of ethylenediaminetetraacetic acid and 8-13g of polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) are added The powder after ball milling is transferred to a high-speed mixer for uniform mixing, 120-150 mL of polyvinyl alcohol solution, 50-80 mL of ethylene glycol and 300-450 mL of methanol are added, and stirring is continued for 30 minutes to form a suspension; the suspension is then spray-dried in a spray dryer, and the air inlet temperature is set to 135°C and the air outlet temperature is set to 160°C to obtain a granular material; In the step, alumina (Al2O3) is used as a matrix material to provide good mechanical strength and high-temperature stability; silicon dioxide (SiO2) enhances the structural stability and corrosion resistance of the material; zirconium oxide (ZrO2) improves the thermal shock resistance and toughness of the material; mullite (3Al2O3·2SiO2) provides excellent high-temperature performance and creep resistance; silicon carbide (SiC) increases thermal conductivity and wear resistance; cerium dioxide can promote densification and improve the microstructure; P123, as an amphiphilic structure, has good surface activity, can reduce the surface tension of the liquid, and has solubilizing and dispersing effects; in addition, the spray drying method used in this step to prepare the granular material can control the size of the generated particles, and the formed particles are usually spherical or approximately spherical and have good fluidity; the spray drying method used in this step is fast, efficient, high-quality, and flexible, and the granular material is made to facilitate subsequent molding.

[0008] S5, placing the material granulated in step S4 into a mold, setting the pressure to 100-700 MPa for pressing, holding the pressure for 15-34 min, to form the desired shape; then pre-burning at about 800-1000 ° C to remove organic matter and initially solidify; sintering in an argon-hydrogen mixed gas containing 5% hydrogen for 2-3 hours at a sintering temperature of 1600-1800 ° C to densify the material and form a stable crystal structure, and then sintering at 5 ° C min -1 The refractory material for hydrogen glass furnace can be obtained by cooling to room temperature at a rate of . This step adopts cold isostatic pressing to ensure higher density and uniformity; the mold uses a flexible mold made of rubber or elastic plastic to ensure that the pressure can be evenly transmitted; the cooling rate is controlled to avoid cracks or deformation caused by sudden temperature drop.

[0009] Preferably: in step S2, 2 g of sodium hydroxide and 0.15 g of ammonium thiosulfate are weighed and dissolved in 12 mL of deionized water, and the copper foil treated in step S1 is immersed in the water. After soaking for 8 minutes, the copper foil is taken out and rinsed to obtain Cu(OH)2 nanowires, and then calcined in a muffle furnace at 320°C for 1.5 hours to obtain CuO nanowires.

[0010] Preferably: in step S2, 3 g of sodium hydroxide and 0.5 g of ammonium thiosulfate are weighed and dissolved in 23 mL of deionized water, and the copper foil treated in step S1 is immersed in the water. After soaking for 15 minutes, the copper foil is taken out and rinsed to obtain Cu(OH)2 nanowires, and then calcined in a muffle furnace at 410°C for 3.1 hours to obtain CuO nanowires.

[0011] Preferably: in the step S3, 0.61 mmol of cobalt nitrate, 0.23 mmol of cesium chloride, 0.23 mmol of ammonium perrhenate and 0.3 g of hexamethylenetetramine are dissolved in 33 mL of deionized water, stirred for 12 min, the CuO nanowires prepared in step S2 are added, soaked for 12 min, and then transferred to a reactor together, calcined at 118 ° C for 8 h, and after cooling, the copper foil with the material is taken out and immersed in ethanol, ultrasonically peeled for 1 h, and centrifuged to obtain Re / Co / Cs-LDH@CuO.

[0012] Preferably: in the step S3, 0.83 mmol of cobalt nitrate, 0.44 mmol of cesium chloride, 0.44 mmol of ammonium perrhenate and 0.5 g of hexamethylenetetramine are dissolved in 45 mL of deionized water, stirred for 23 min, the CuO nanowires prepared in step S2 are added, soaked for 16 min, and then transferred to a reactor together, calcined at 148 ° C for 10 h, and after cooling, the copper foil with the material is taken out and immersed in ethanol, ultrasonically peeled for 1 h, and centrifuged to obtain Re / Co / Cs-LDH@CuO.

[0013] Preferably: in the step S4, 5 g of Re / Co / Cs-LDH@CuO prepared in step S3, 33 g of aluminum oxide, 5 g of silicon dioxide, 11 g of zirconium oxide, 4 g of mullite, 17 g of silicon carbide, 6 g of cerium dioxide, 7 g of titanium oxide, 2 g of ethylenediaminetetraacetic acid and 8 g of polyethylene oxide-polypropylene oxide-polyethylene oxide are added to a ball mill and ball milled for 35 minutes; the powder after ball milling is transferred to a high-speed mixer for uniform mixing, 120 mL of polyvinyl alcohol solution, 50 mL of ethylene glycol and 300 mL of methanol are added, and stirring is continued for 30 minutes to form a suspension; the suspension is then spray dried by a spray dryer, and the inlet temperature is set to 135°C and the outlet temperature is set to 160°C to obtain a granular material.

[0014] Preferably: in the step S4, 7g of Re / Co / Cs-LDH@CuO prepared in step S3, 41g of aluminum oxide, 8g of silicon dioxide, 13g of zirconium oxide, 6g of mullite, 23g of silicon carbide, 8g of cerium dioxide, 11g of titanium oxide, 5g of ethylenediaminetetraacetic acid and 13g of polyethylene oxide-polypropylene oxide-polyethylene oxide are added to a ball mill and ball milled for 45min; the powder after ball milling is transferred to a high-speed mixer for uniform mixing, 150mL of polyvinyl alcohol solution, 80mL of ethylene glycol and 450mL of methanol are added, and stirring is continued for 30min to form a suspension; the suspension is then spray dried by a spray dryer, and the inlet temperature is set to 135°C and the outlet temperature is set to 160°C to obtain a granular material.

[0015] Preferably, in step S5, the material granulated in step S4 is placed in a mold, and the pressure is set to 100 MPa for pressing, and the pressure holding time is 15 minutes to form the desired shape; then, it is pre-sintered at about 800°C to remove organic matter and initially solidify; sintered in an argon-hydrogen mixed gas containing 5% hydrogen for 2 hours, and the sintering temperature is 1600°C to densify the material and form a stable crystal structure, and then heated at 5°C min -1 By cooling to room temperature at a rate of, the refractory material for the hydrogen glass furnace can be obtained.

[0016] Preferably, in step S5, the material granulated in step S4 is placed in a mold, and the pressure is set to 700 MPa for pressing, and the pressure holding time is 34 minutes to form the desired shape; then, it is pre-sintered at about 1000°C to remove organic matter and initially solidify; sintered in an argon-hydrogen mixed gas containing 5% hydrogen for 3 hours, and the sintering temperature is 1800°C to densify the material and form a stable crystal structure, and then heated at 5°C min -1 By cooling to room temperature at a rate of, the refractory material for the hydrogen glass furnace can be obtained.

[0017] The benefits of the present invention are:

[0018] 1. The refractory material prepared by the present invention can work stably for a long time in a high temperature environment without significant phase change or decomposition.

[0019] 2. The refractory material prepared by the present invention has good thermal shock resistance, so that the material can withstand frequent temperature changes.

[0020] 3. The refractory material prepared by the present invention exhibits excellent anti-oxidation performance in a hydrogen combustion environment, preventing the surface of the material from being eroded by oxidation.

[0021] 4. The refractory material prepared by the present invention has high mechanical strength and wear resistance, which greatly improves the reliability and durability of the material under harsh working conditions.

[0022] 5. The preparation process of the present invention is simple to operate and the product price is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 This is a scanning electron microscope image of the Cu(OH)2 nanowires prepared in the present invention.

[0025] Figure 2 This is a scanning electron microscope image of the CuO nanowires prepared in the present invention.

[0026] Figure 3 This is a scanning electron microscope image of Re / Co / Cs-LDH@CuO prepared in Example 2 of the present invention.

[0027] Figure 4 This is a scanning electron microscope image of Re / Cs-LDH@CuO prepared in Comparative Example 1 of the present invention.

[0028] Figure 5 This is a scanning electron microscope image of Re / Co-LDH@CuO prepared in Comparative Example 2 of the present invention.

[0029] Figure 6 This is a scanning electron microscope image of Co / Cs-LDH@CuO prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the content of the present invention and are not used to limit the present invention.

[0031] Example 1

[0032] S1. Take 5 mL of hydrochloric acid, dilute it to 20 mL with ethanol, immerse the copper foil until the solution turns yellow, take out the copper foil, rinse it with ethanol, then immerse it in acetone for 5 minutes, rinse it with ethanol, then immerse it in ethanol for 8 minutes, and you can get a clean copper foil; all solutions in this step need to be prepared before use to avoid re-oxidation.

[0033] S2. Weigh 2 g of sodium hydroxide and 0.15 g of ammonium thiosulfate and dissolve them in 12 mL of deionized water. Immerse the copper foil treated in step S1 and soak for 8 minutes, then take it out and rinse it to obtain Cu(OH)2 nanowires. Then calcine it in a muffle furnace at 320°C for 1.5 hours to obtain CuO nanowires. In this step, the Cu(OH)2 nanowires are calcined in a muffle furnace for rapid dehydration to prepare more resilient CuO nanowires.

[0034] S3, 0.61mmol of cobalt nitrate, 0.23mmol of cesium chloride, 0.23mmol of ammonium perrhenate and 0.3g of hexamethylenetetramine were dissolved in 33mL of deionized water, stirred for 12min, and the CuO nanowires prepared in step S2 were added and soaked for 12min, then transferred to a reactor together, calcined at 118°C for 8h, and after cooling, the copper foil with the material was taken out and immersed in ethanol, ultrasonically peeled for 1h, and centrifuged and dried to obtain Re / Co / Cs-LDH@CuO. This material utilizes the one-dimensional structure of copper oxide nanowires, and the outer layer of the nanowires is coated with Re, Co and Cs metal nanoparticles. The three metal particles are uniformly attached to the nanowires through hydrothermal reaction. As an additive for refractory materials, it can improve the toughness and thermal shock resistance of refractory materials to ensure that the refractory materials will not crack or break in frequent temperature changes.

[0035] S4, 5g of Re / Co / Cs-LDH@CuO prepared in step S3, 33g of aluminum oxide, 5g of silicon dioxide, 11g of zirconium oxide, 4g of mullite, 17g of silicon carbide, 6g of cerium dioxide, 7g of titanium oxide, 2g of ethylenediaminetetraacetic acid and 8g of polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) were added to a ball mill and ball milled for 35min; the powder after ball milling was transferred to a high-speed mixer for uniform mixing, 120mL of polyvinyl alcohol solution, 50mL of ethylene glycol and 300mL of methanol were added, and stirring was continued for 30min to form a suspension; the suspension was then spray dried by a spray dryer, and the inlet air temperature was set to 135°C and the outlet air temperature was set to 160°C to obtain a granular material; in this step, aluminum oxide (Al2O3) was used as the matrix material, Provide good mechanical strength and high temperature stability; silicon dioxide (SiO2) enhances the structural stability and corrosion resistance of the material; zirconium oxide (ZrO2) improves the thermal shock resistance and toughness of the material; mullite (3Al2O3·2SiO2) provides excellent high temperature performance and creep resistance; silicon carbide (SiC) increases thermal conductivity and wear resistance; cerium dioxide can promote densification and improve the microstructure; P123 as an amphiphilic structure has good surface activity, can reduce the surface tension of the liquid, and has solubilizing and dispersing effects; in addition, the use of spray drying method to prepare granular materials in this step can control the size of the generated particles, and the formed particles are usually spherical or approximately spherical and have good fluidity; the spray drying method used in this step is fast, efficient, high-quality and flexible, and the granular material is made to facilitate subsequent molding.

[0036] S5, placing the material granulated in step S4 into a mold, setting the pressure to 100 MPa for pressing, holding the pressure for 15 minutes, and forming the desired shape; then pre-burning at about 800 ° C to remove organic matter and initially solidify; sintering in an argon-hydrogen mixed gas containing 5% hydrogen for 2 hours at a sintering temperature of 1600 ° C to densify the material and form a stable crystal structure, and then sintering at 5 ° C min -1 The refractory material for hydrogen glass furnace can be obtained by cooling to room temperature at a rate of . This step adopts cold isostatic pressing to ensure higher density and uniformity; the mold uses a flexible mold made of rubber or elastic plastic to ensure that the pressure can be evenly transmitted; the cooling rate is controlled to avoid cracks or deformation caused by sudden temperature drop.

[0037] Figure 1 This is a scanning electron microscope image of the Cu(OH)2 nanowires prepared in the present invention. Figure 2This is a scanning electron microscope image of the CuO nanowires prepared by the present invention. It can be seen from the figure that the Cu(OH)2 nanowires are rapidly dehydrated in the muffle furnace and become curved CuO nanowires. Using them as a skeleton and attaching Re / Co / Cs-LDH will greatly improve the toughness of the refractory material.

[0038] Example 2

[0039] S1. Take 12mL of hydrochloric acid, dilute it to 33mL with ethanol, immerse the copper foil until the solution turns yellow, take out the copper foil, rinse it with ethanol, then immerse it in acetone for 11 minutes, rinse it with ethanol, then immerse it in ethanol for 16 minutes, and you can get a clean copper foil; all solutions in this step need to be prepared before use to avoid re-oxidation.

[0040] S2. Weigh 3 g of sodium hydroxide and 0.5 g of ammonium thiosulfate and dissolve them in 23 mL of deionized water. Immerse the copper foil treated in step S1 and soak for 15 min. Then take it out and rinse it to obtain Cu(OH)2 nanowires. Then calcine it in a muffle furnace at 410°C for 3.1 h to obtain CuO nanowires. In this step, the Cu(OH)2 nanowires are calcined in a muffle furnace for rapid dehydration to prepare more resilient CuO nanowires.

[0041] S3, 0.83mmol of cobalt nitrate, 0.44mmol of cesium chloride, 0.44mmol of ammonium perrhenate and 0.5g of hexamethylenetetramine were dissolved in 45mL of deionized water, stirred for 23min, and the CuO nanowires prepared in step S2 were added and soaked for 16min, then transferred to a reactor together, calcined at 148°C for 10h, and after cooling, the copper foil with the material was taken out and immersed in ethanol, ultrasonically peeled for 1h, and centrifuged and dried to obtain Re / Co / Cs-LDH@CuO. This material utilizes the one-dimensional structure of copper oxide nanowires, and the outer layer of the nanowires is coated with Re, Co and Cs metal nanoparticles. The three metal particles are uniformly attached to the nanowires through hydrothermal reaction. As an additive for refractory materials, it can improve the toughness and thermal shock resistance of refractory materials to ensure that the refractory materials will not crack or break in frequent temperature changes.

[0042] S4, 7g of Re / Co / Cs-LDH@CuO prepared in step S3, 41g of aluminum oxide, 8g of silicon dioxide, 13g of zirconium oxide, 6g of mullite, 23g of silicon carbide, 8g of cerium dioxide, 11g of titanium oxide, 5g of ethylenediaminetetraacetic acid and 13g of polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) were added to a ball mill and ball milled for 45min; the powder after ball milling was transferred to a high-speed mixer and mixed evenly, 150mL of polyvinyl alcohol solution, 80mL of ethylene glycol and 450mL of methanol were added, and stirring was continued for 30min to form a suspension; the suspension was then spray dried by a spray dryer, and the inlet air temperature was set to 135°C and the outlet air temperature was set to 160°C to obtain a granular material; in this step, aluminum oxide (Al2O3) was used as the matrix material , providing good mechanical strength and high temperature stability; silicon dioxide (SiO2) enhances the structural stability and corrosion resistance of the material; zirconium oxide (ZrO2) improves the thermal shock resistance and toughness of the material; mullite (3Al2O3·2SiO2) provides excellent high temperature performance and creep resistance; silicon carbide (SiC) increases thermal conductivity and wear resistance; cerium dioxide can promote densification and improve the microstructure; P123 as an amphiphilic structure has good surface activity, can reduce the surface tension of the liquid, and has solubilizing and dispersing effects; in addition, the use of spray drying method to prepare granular materials in this step can control the size of the generated particles, and the formed particles are usually spherical or approximately spherical and have good fluidity; the spray drying method used in this step is fast, efficient, high-quality and flexible, and is made into granular materials for subsequent molding.

[0043] S5, placing the material granulated in step S4 into a mold, setting the pressure to 700MPa for pressing, holding the pressure for 34min, to form the desired shape; then pre-sintering at about 1000°C to remove organic matter and initially solidify; sintering in an argon-hydrogen mixed gas containing 5% hydrogen for 3h at a sintering temperature of 1800°C to densify the material and form a stable crystal structure, then sintering at 5°C min -1 The refractory material for hydrogen glass furnace can be obtained by cooling to room temperature at a rate of . This step adopts cold isostatic pressing to ensure higher density and uniformity; the mold uses a flexible mold made of rubber or elastic plastic to ensure that the pressure can be evenly transmitted; the cooling rate is controlled to avoid cracks or deformation caused by sudden temperature drop.

[0044] Comparative Example 1: Except that 0.83 mmol of cobalt nitrate is not added in step S3, the remaining steps are the same as those in Example 2.

[0045] Comparative Example 2: Except that 0.44 mmol of cesium chloride is not added in step S3, the remaining steps are the same as those in Example 2.

[0046] Comparative Example 3: Except that 0.44 mmol of ammonium perrhenate is not added in step S3, the remaining steps are the same as those in Example 2.

[0047] Figure 3 This is a scanning electron microscope image of Re / Co / Cs-LDH@CuO prepared in Example 2 of the present invention. Figure 4 This is a scanning electron microscope image of Re / Cs-LDH@CuO prepared in Comparative Example 1 of the present invention. Figure 5 This is a scanning electron microscope image of Re / Co-LDH@CuO prepared in Comparative Example 2 of the present invention. Figure 6 This is a scanning electron microscope image of Co / Cs-LDH@CuO prepared in comparative example 3 of the present invention. It can be seen from the figure that under the same conditions, the attachment of different metal elements will make the nanowires different in thickness and appearance. The outer layer of the nanowires is simultaneously coated with three kinds of metal nanoparticles of Re, Co and Cs, and there is a synergistic effect between the three metal elements. From the observation of the morphology, it can be seen that the surface area of ​​Re / Co / Cs-LDH@CuO is larger, and when the refractory material is subsequently prepared, it can be better integrated with other raw materials, and the anti-expansion effect is higher. Therefore, the toughness and thermal shock resistance of the refractory material can be improved to ensure that the refractory material will not crack in frequent temperature changes. The addition of Re / Co / Cs-LDH@CuO helps to improve the high temperature strength and creep resistance of the material, and is enough to enhance the density of the material, thereby increasing the load softening temperature.

[0048] Example 3

[0049] S1. Take 8 mL of hydrochloric acid, dilute it to 27 mL with ethanol, immerse the copper foil until the solution turns yellow, take out the copper foil, rinse it with ethanol, then immerse it in acetone for 9 minutes, rinse it with ethanol, then immerse it in ethanol for 14 minutes, and you can get a clean copper foil; all solutions in this step need to be prepared before use to avoid re-oxidation.

[0050] S2. Weigh 3 g of sodium hydroxide and 0.22 g of ammonium thiosulfate and dissolve them in 20 mL of deionized water. Immerse the copper foil treated in step S1 and soak for 9 minutes, then take it out and rinse it to obtain Cu(OH)2 nanowires. Then calcine it in a muffle furnace at 405°C for 1.9 hours to obtain CuO nanowires. In this step, the Cu(OH)2 nanowires are calcined in a muffle furnace for rapid dehydration to prepare more resilient CuO nanowires.

[0051] S3, 0.77mmol of cobalt nitrate, 0.28mmol of cesium chloride, 0.33mmol of ammonium perrhenate and 0.4g of hexamethylenetetramine were dissolved in 39mL of deionized water, stirred for 18min, and the CuO nanowires prepared in step S2 were added and soaked for 15min, then transferred to a reactor together, calcined at 138°C for 9h, and after cooling, the copper foil with the material was taken out and immersed in ethanol, ultrasonically peeled for 1h, and centrifuged and dried to obtain Re / Co / Cs-LDH@CuO. This material utilizes the one-dimensional structure of copper oxide nanowires, and the outer layer of the nanowires is coated with Re, Co and Cs metal nanoparticles. The three metal particles are uniformly attached to the nanowires through hydrothermal reaction. As an additive for refractory materials, it can improve the toughness and thermal shock resistance of refractory materials to ensure that the refractory materials will not crack or break in frequent temperature changes.

[0052] S4, add 6g of Re / Co / Cs-LDH@CuO prepared in step S3, 39g of aluminum oxide, 7g of silicon dioxide, 12g of zirconium oxide, 5g of mullite, 19g of silicon carbide, 7g of cerium dioxide, 8g of titanium oxide, 4g of ethylenediaminetetraacetic acid and 11g of polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) into a ball mill and mill for 38min; transfer the powder after uniform ball milling to a high-speed mixer for uniform mixing, add 140mL of polyvinyl alcohol solution, 70mL of ethylene glycol and 400mL of methanol, and continue stirring for 30min to form a suspension; then spray dry the suspension through a spray dryer, set the inlet air temperature to 135°C and the outlet air temperature to 160°C, and obtain a granular material; in this step, aluminum oxide (Al2O3) is used as the matrix material , providing good mechanical strength and high temperature stability; silicon dioxide (SiO2) enhances the structural stability and corrosion resistance of the material; zirconium oxide (ZrO2) improves the thermal shock resistance and toughness of the material; mullite (3Al2O3·2SiO2) provides excellent high temperature performance and creep resistance; silicon carbide (SiC) increases thermal conductivity and wear resistance; cerium dioxide can promote densification and improve the microstructure; P123 as an amphiphilic structure has good surface activity, can reduce the surface tension of the liquid, and has solubilizing and dispersing effects; in addition, the use of spray drying method to prepare granular materials in this step can control the size of the generated particles, and the formed particles are usually spherical or approximately spherical and have good fluidity; the spray drying method used in this step is fast, efficient, high-quality and flexible, and is made into granular materials for subsequent molding.

[0053] S5, placing the material granulated in step S4 into a mold, setting the pressure to 500MPa for pressing, holding the pressure for 19min, forming the desired shape; then pre-burning at about 900°C to remove organic matter and initially solidify; sintering in an argon-hydrogen mixed gas containing 5% hydrogen for 3h at a sintering temperature of 1700°C to densify the material and form a stable crystal structure, and then calcining at 5°C min -1 The refractory material for hydrogen glass furnace can be obtained by cooling to room temperature at a rate of . This step adopts cold isostatic pressing to ensure higher density and uniformity; the mold uses a flexible mold made of rubber or elastic plastic to ensure that the pressure can be evenly transmitted; the cooling rate is controlled to avoid cracks or deformation caused by sudden temperature drop.

[0054] Comparative Example 4: Except that 0.28 mmol of cesium chloride is not added in step S3, the remaining steps are the same as those in Example 3.

[0055] Comparative Example 5: Except that 0.77 mmol of cobalt nitrate is not added in step S3, the remaining steps are the same as those in Example 3.

[0056] Comparative Example 6: Except that 0.33 mmol of ammonium perrhenate is not added in step S3, the remaining steps are the same as those in Example 3.

[0057] The load-softening temperature (LST) of a refractory material refers to the temperature at which the material begins to deform and exhibits plastic flow under certain load conditions. This parameter is an important indicator for evaluating the high-temperature strength and creep resistance of refractory materials, and is crucial for predicting the performance of the material in actual use. The present invention can significantly improve the load-softening temperature of the material through reasonable component design, microstructure optimization and sintering process control. The load-softening temperature reflects the stability of the material under the combined action of high temperature and stress. High-temperature strength: The higher the load-softening temperature, the better the mechanical strength of the material at high temperature. Creep resistance: This temperature also indirectly reflects the material's ability to resist long-term creep. Service life: A high load-softening temperature means that the material can maintain its shape and function at higher temperatures, thereby extending its service life. The test standard used in the present invention is the Chinese national standard: GB / T 7321. Prepare the sample into a standard cylindrical shape (diameter: 40mm±0.5mm height: 40mm±0.5mm), place the sample in a special test equipment, apply a load of 0.2MPa, heat the sample at a constant rate (such as 5℃ / min), and monitor its deformation. When the compressive deformation of the sample reaches 0.6%, record the temperature at this time as the load softening temperature. The room temperature compressive strength of refractory materials refers to the ability of materials to resist compressive loads without damage under room temperature conditions. This parameter is one of the important indicators for evaluating the mechanical properties of refractory materials and is crucial for predicting their performance in actual use. Room temperature compressive strength refers to the maximum stress that a material can withstand under axial compressive loads at room temperature. Mechanical strength: reflects the material's ability to resist damage when under pressure. Structural stability: High compressive strength means that the material can maintain good structural stability in applications such as high-temperature furnace linings and kilns. Test standard: Chinese national standard GB / T 3001. Prepare a cylinder that meets standard dimensions (diameter 40mm±0.5mm, height 40mm±0.5mm), and ensure that the end face of the sample is flat and smooth without obvious defects. Dry the sample in an oven at 110℃±℃ to constant weight. Place the dried sample between the upper and lower platens of a universal testing machine, ensuring that the axis of the sample is perpendicular to the platens. Apply an axial compressive load at a constant rate (such as 0.5MPa / s) until the sample is destroyed. To eliminate contingency, each sample is tested 5 times. Test the load softening temperature and room temperature compressive strength of the refractory material for a hydrogen glass furnace prepared by the present invention.

[0058] Table 1. Test results of load softening temperature and room temperature compressive strength

[0059] Softening temperature under load Normal temperature compressive strength Example 2 1890±5℃ 703±4MPa Example 3 1875±6℃ 694±6MPa Comparative Example 4 1420±3℃ 433±7MPa Comparative Example 5 1503±4℃ 521±5MPa Comparative Example 6 1399±8℃ 491±3MPa

[0060] Table 1 shows the refractoriness under load and room temperature compressive strength of the refractory material for hydrogen energy glass furnace prepared by the present invention. By comparison, it is found that the refractoriness under load and room temperature compressive strength of the refractory material prepared in Examples 2 and 3 are better than those in Comparative Examples 4-6, indicating that the three metal elements Re, Co and Cs involved in the additive Re / Co / Cs-LDH@CuO are indispensable. Combined with the analysis of the scanning graph, it can be seen that the three elements Re, Co and Cs in Re / Co / Cs-LDH@CuO have a certain synergistic effect, and attached around the CuO nanowires, they can play a role in adjusting the material structure and greatly improve the mechanical properties of the material.

[0061] Example 4

[0062] S1. Take 9 mL of hydrochloric acid, dilute it to 22 mL with ethanol, immerse the copper foil until the solution turns yellow, take out the copper foil, rinse it with ethanol, then immerse it in acetone for 9 minutes, rinse it with ethanol, then immerse it in ethanol for 13 minutes, and you can get a clean copper foil; all solutions in this step need to be prepared before use to avoid re-oxidation.

[0063] S2. Weigh 3 g of sodium hydroxide and 0.33 g of ammonium thiosulfate and dissolve them in 19 mL of deionized water. Immerse the copper foil treated in step S1 and soak for 11 minutes, then take it out and rinse it to obtain Cu(OH)2 nanowires. Then calcine it in a muffle furnace at 360°C for 1.9 hours to obtain CuO nanowires. In this step, the Cu(OH)2 nanowires are calcined in a muffle furnace for rapid dehydration to prepare more resilient CuO nanowires.

[0064] S3, 0.73mmol of cobalt nitrate, 0.35mmol of cesium chloride, 0.36mmol of ammonium perrhenate and 0.4g of hexamethylenetetramine were dissolved in 38mL of deionized water, stirred for 19min, and the CuO nanowires prepared in step S2 were added and soaked for 14min, then transferred to a reactor together, calcined at 128°C for 8-10h, and after cooling, the copper foil with the material was taken out and immersed in ethanol, ultrasonically peeled for 1h, and centrifuged and dried to obtain Re / Co / Cs-LDH@CuO. This material utilizes the one-dimensional structure of copper oxide nanowires, and the outer layer of the nanowires is coated with Re, Co and Cs metal nanoparticles. The three metal particles are uniformly attached to the nanowires through hydrothermal reaction. As an additive for refractory materials, it can improve the toughness and thermal shock resistance of refractory materials to ensure that the refractory materials will not crack or break in frequent temperature changes.

[0065] S4, 5.9g of Re / Co / Cs-LDH@CuO prepared in step S3, 37g of aluminum oxide, 7g of silicon dioxide, 12g of zirconium oxide, 5g of mullite, 18g of silicon carbide, 7g of cerium dioxide, 8g of titanium oxide, 3g of ethylenediaminetetraacetic acid and 11g of polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) were added to a ball mill and ball milled for 37min; the powder after ball milling was transferred to a high-speed mixer and mixed evenly, 133mL of polyvinyl alcohol solution, 70mL of ethylene glycol and 390mL of methanol were added, and stirring was continued for 30min to form a suspension; the suspension was then spray-dried by a spray dryer, and the inlet air temperature was set to 135°C and the outlet air temperature was set to 160°C to obtain a granular material; in this step, aluminum oxide (Al2O3) was used as the matrix material. The material provides good mechanical strength and high temperature stability; silicon dioxide (SiO2) enhances the structural stability and corrosion resistance of the material; zirconium oxide (ZrO2) improves the thermal shock resistance and toughness of the material; mullite (3Al2O3·2SiO2) provides excellent high temperature performance and creep resistance; silicon carbide (SiC) increases thermal conductivity and wear resistance; cerium dioxide can promote densification and improve the microstructure; P123 as an amphiphilic structure has good surface activity, can reduce the surface tension of the liquid, and has solubilizing and dispersing effects; in addition, the use of spray drying method to prepare granular materials in this step can control the size of the generated particles, and the formed particles are usually spherical or approximately spherical and have good fluidity; the spray drying method used in this step is fast, efficient, high-quality and flexible, and the granular material is made to facilitate subsequent molding.

[0066] S5, placing the material granulated in step S4 into a mold, setting the pressure to 600MPa for pressing, holding the pressure for 17min, forming the desired shape; then pre-burning at about 900°C to remove organic matter and initially solidify; sintering in an argon-hydrogen mixed gas containing 5% hydrogen for 2h at a sintering temperature of 1700°C to densify the material and form a stable crystal structure, and then calcining at 5°C min -1 The refractory material for hydrogen glass furnace can be obtained by cooling to room temperature at a rate of . This step adopts cold isostatic pressing to ensure higher density and uniformity; the mold uses a flexible mold made of rubber or elastic plastic to ensure that the pressure can be evenly transmitted; the cooling rate is controlled to avoid cracks or deformation caused by sudden temperature drop.

[0067] Comparative Example 7: Except that 3 g of ethylenediaminetetraacetic acid is not added in step S4, the remaining steps are the same as those in Example 4.

[0068] Comparative Example 8: Except that 11 g of polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) is not added in step S4, the remaining steps are the same as those in Example 4.

[0069] Comparative Example 9: Except that Re / Co / Cs-LDH@CuO is not added in step S4, the remaining steps are the same as those in Example 4.

[0070] Table 2 shows the wear amount of the refractory material for hydrogen glass furnace prepared by the present invention on the Taber abrasion tester, with the grinding wheel rotating 1000 times. The heating permanent line change (1450℃×2h) / % is 0.1, and the test of thermal shock resistance adopts the following method: the refractory material is treated at 1450℃ for 2h to measure its flexural strength, the flexural strength is P1, and then after keeping at 1100℃ for 20min, it is quenched in 20℃ cold water, and repeated 30 times, the flexural strength is P2. By comparing the test data in Table 1, it can be seen that the addition of ethylenediaminetetraacetic acid, Re / Co / Cs-LDH@CuO and polyethylene oxide-polypropylene oxide-polyethylene oxide (P123) has a positive effect on improving the thermal shock resistance of the refractory material prepared by the present invention. In particular, Re / Co / Cs-LDH@CuO has a great influence on improving the mechanical properties of the material. In Comparative Example 9, Re / Co / Cs-LDH@CuO was not added, and the mechanical properties of the prepared refractory material were extremely poor.

[0071] Table 2

[0072] Wear amount g P1 P2 Example 4 45.3±0.8g 26.6±0.9MPa 20.1±0.9MPa Comparative Example 7 68.2±0.3g 18.3±0.8MPa 11.5±0.2MPa Comparative Example 8 69.8±0.6g 17.6±0.4MPa 10.9±0.3MPa Comparative Example 9 70.1±0.7g 16.4±0.2MPa 9.8±0.5MPa

[0073] The embodiments described above are merely descriptions of the preparation process of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solution of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A refractory material for a hydrogen glass furnace, characterized in that: The specific preparation steps are as follows: S1. Take 5-12mL of hydrochloric acid, dilute it to 20-33mL with ethanol, immerse it in the copper foil, soak it until the solution turns yellow, take out the copper foil, rinse it with ethanol, then immerse it in acetone for 5-11min, rinse it with ethanol, then immerse it in ethanol for 8-16min, and then get the clean copper foil; S2, weigh 2-3g of sodium hydroxide and 0.15-0.5g of ammonium thiosulfate, dissolve them in 12-23mL of deionized water, immerse the copper foil treated in step S1, soak for 8-15min, take out and rinse, then obtain Cu(OH)2 nanowires, and then calcine in a muffle furnace at 320-410℃ for 1.5-3.1h to obtain CuO nanowires; S3, dissolving 0.61-0.83 mmol of cobalt nitrate, 0.23-0.44 mmol of cesium chloride, 0.23-0.44 mmol of ammonium perrhenate and 0.3-0.5 g of hexamethylenetetramine in 33-45 mL of deionized water, stirring for 12-23 min, adding the CuO nanowires prepared in step S2, soaking for 12-16 min, then transferring them together to a reactor, calcining at 118-148 ° C for 8-10 h, taking out the copper foil with the material after cooling, immersing it in ethanol, ultrasonically peeling for 1 h, and centrifuging and drying to obtain Re / Co / Cs-LDH@CuO; S4, 5-7g of Re / Co / Cs-LDH@CuO prepared in step S3, 33-41g of aluminum oxide, 5-8g of silicon dioxide, 11-13g of zirconium oxide, 4-6g of mullite, 17-23g of silicon carbide, 6-8g of cerium dioxide, 7-11g of titanium oxide, 2-5g of ethylenediaminetetraacetic acid and 8-13g of polyethylene oxide-polypropylene oxide-polyethylene oxide are added to a ball mill and ball milled for 35-45min; the powder after ball milling is transferred to a high-speed mixer for uniform mixing, 120-150mL of polyvinyl alcohol solution, 50-80mL of ethylene glycol and 300-450mL of methanol are added, and stirring is continued for 30min to form a suspension; the suspension is then spray dried by a spray dryer, and the air inlet temperature is set to 135°C and the air outlet temperature is set to 160°C to obtain a granular material; S5, placing the material granulated in step S4 into a mold, setting the pressure to 100-700 MPa for pressing, holding the pressure for 15-34 min, to form the desired shape; then pre-burning at about 800-1000 ° C to remove organic matter and initially solidify; sintering in an argon-hydrogen mixed gas containing 5% hydrogen for 2-3 hours at a sintering temperature of 1600-1800 ° C to densify the material and form a stable crystal structure, and then sintering at 5 ° C min -1 By cooling to room temperature at a rate of, the refractory material for the hydrogen glass furnace can be obtained.

2. The refractory material for a hydrogen energy glass furnace according to claim 1, characterized in that: In the step S2, 2 g of sodium hydroxide and 0.15 g of ammonium thiosulfate are weighed and dissolved in 12 mL of deionized water, and the copper foil treated in step S1 is immersed in the water. After soaking for 8 minutes, the copper foil is taken out and rinsed to obtain Cu(OH)2 nanowires, and then calcined in a muffle furnace at 320°C for 1.5 hours to obtain CuO nanowires.

3. A refractory material for a hydrogen glass furnace according to claim 1 or 2, characterized in that: In the step S2, 3 g of sodium hydroxide and 0.5 g of ammonium thiosulfate are weighed and dissolved in 23 mL of deionized water, and the copper foil treated in step S1 is immersed in the water. After soaking for 15 minutes, the copper foil is taken out and rinsed to obtain Cu(OH)2 nanowires, and then calcined in a muffle furnace at 410°C for 3.1 hours to obtain CuO nanowires.

4. The refractory material for a hydrogen glass furnace according to claim 1, characterized in that: In the step S3, 0.61 mmol of cobalt nitrate, 0.23 mmol of cesium chloride, 0.23 mmol of ammonium perrhenate and 0.3 g of hexamethylenetetramine are dissolved in 33 mL of deionized water, stirred for 12 min, and the CuO nanowires prepared in step S2 are added and soaked for 12 min, and then transferred to a reactor together, calcined at 118° C. for 8 h, and after cooling, the copper foil with the material is taken out and immersed in ethanol, ultrasonically peeled for 1 h, and centrifuged to obtain Re / Co / Cs-LDH@CuO.

5. A refractory material for a hydrogen glass furnace according to claim 1 or 4, characterized in that: In the step S3, 0.83 mmol of cobalt nitrate, 0.44 mmol of cesium chloride, 0.44 mmol of ammonium perrhenate and 0.5 g of hexamethylenetetramine are dissolved in 45 mL of deionized water, stirred for 23 min, and the CuO nanowires prepared in step S2 are added and soaked for 16 min, and then transferred to a reactor together, calcined at 148° C. for 10 h, and after cooling, the copper foil with the material is taken out and immersed in ethanol, ultrasonically peeled for 1 h, and centrifuged and dried to obtain Re / Co / Cs-LDH@CuO.

6. The refractory material for a hydrogen glass furnace according to claim 1, characterized in that: In the step S4, 5 g of Re / Co / Cs-LDH@CuO prepared in step S3, 33 g of aluminum oxide, 5 g of silicon dioxide, 11 g of zirconium oxide, 4 g of mullite, 17 g of silicon carbide, 6 g of cerium dioxide, 7 g of titanium oxide, 2 g of ethylenediaminetetraacetic acid and 8 g of polyethylene oxide-polypropylene oxide-polyethylene oxide are added to a ball mill and ball milled for 35 minutes; the powder after ball milling is transferred to a high-speed mixer for uniform mixing, 120 mL of polyvinyl alcohol solution, 50 mL of ethylene glycol and 300 mL of methanol are added, and stirring is continued for 30 minutes to form a suspension; then the suspension is spray dried by a spray dryer, and the inlet air temperature is set to 135° C. and the outlet air temperature is set to 160° C. to obtain a granular material.

7. A refractory material for a hydrogen energy glass furnace according to claim 1 or 6, characterized in that: In the step S4, 7 g of Re / Co / Cs-LDH@CuO prepared in step S3, 41 g of aluminum oxide, 8 g of silicon dioxide, 13 g of zirconium oxide, 6 g of mullite, 23 g of silicon carbide, 8 g of cerium dioxide, 11 g of titanium oxide, 5 g of ethylenediaminetetraacetic acid and 13 g of polyethylene oxide-polypropylene oxide-polyethylene oxide are added to a ball mill and ball milled for 45 minutes; the powder after ball milling is transferred to a high-speed mixer for uniform mixing, 150 mL of polyvinyl alcohol solution, 80 mL of ethylene glycol and 450 mL of methanol are added, and stirring is continued for 30 minutes to form a suspension; then the suspension is spray dried by a spray dryer, and the inlet air temperature is set to 135° C. and the outlet air temperature is set to 160° C. to obtain a granular material.

8. The refractory material for a hydrogen energy glass furnace according to claim 1, characterized in that: In the step S5, the material granulated in the step S4 is placed in a mold, and the pressure is set to 100 MPa for pressing, and the pressure holding time is 15 minutes to form the desired shape; then it is pre-sintered at about 800°C to remove organic matter and initially solidify; sintered in an argon-hydrogen mixed gas containing 5% hydrogen for 2 hours, and the sintering temperature is 1600°C to densify the material and form a stable crystal structure, and then sintered at 5°C min -1 By cooling to room temperature at a rate of, the refractory material for the hydrogen glass furnace can be obtained.

9. The refractory material for a hydrogen energy glass furnace according to claim 1, characterized in that: In the step S5, the material granulated in the step S4 is placed in a mold, and the pressure is set to 700 MPa for pressing, and the pressure holding time is 34 minutes to form the desired shape; then it is pre-sintered at about 1000°C to remove organic matter and initially solidify; sintered in an argon-hydrogen mixed gas containing 5% hydrogen for 3 hours at a sintering temperature of 1800°C to densify the material and form a stable crystal structure, and then sintered at 5°C min -1 By cooling to room temperature at a rate of, the refractory material for the hydrogen glass furnace can be obtained.

10. The refractory material for a hydrogen glass furnace prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Product including carbon nano-tube and method for purifying fluid with the carbon nano-tube

    CN101198542A

  • Copper-based and silicon-based composite catalyst as well as preparation method and application thereof

    CN112742396A

  • Metal delivery system for nanoparticle manufacture

    US20060229197A1

  • Sinterable ceramic compositions

    US5175132A

Cited By

  • High-strength anti-cracking corrosion-resistant castable and preparation method thereof

    CN122010540A